2010
DOI: 10.1111/j.1742-4658.2010.07898.x
|View full text |Cite
|
Sign up to set email alerts
|

Diol dehydratase‐reactivating factor is a reactivase – evidence for multiple turnovers and subunit swapping with diol dehydratase

Abstract: Adenosylcobalamin-dependent diol dehydratase (DD) undergoes suicide inactivation by glycerol, one of its physiological substrates, resulting in the irreversible cleavage of the coenzyme Co-C bond. The damaged cofactor remains tightly bound to the active site. The DD-reactivating factor reactivates the inactivated holoenzyme in the presence of ATP and Mg 2+ by mediating the exchange of the tightly bound damaged cofactor for free intact coenzyme. In this study, we demonstrated that this reactivating factor media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…There was no significant difference in 3-HPA as the bioconversion time increased further. The 3-HPA bioconversion was very rapid, in that about 90% of this product was produced within 0.5 h. The dhaB enzyme, which converts glycerol to 3-HPA and uses vitamin B 12 as a cofactor, is eventually inactivated because the cells cannot regenerate coenzyme B 12 ; instead the catalytic cycle is interrupted by the formation of 5'-deoxyadenosine and the catalytically inactive cobalamin [22], and the altered cofactor remains tightly bound to the active site [23]. A dhaB-reactivating factor in Klebsiella reactivates the inactivated enzyme-bound cyanocobalamin in the presence of free vitamin B 12 , adenosine triphosphate (ATP), and Mg 2+ by mediating the exchange of the tightly bound altered cofactor for a free intact cofactor [24].…”
Section: The Effect Of Conversion Timementioning
confidence: 99%
“…There was no significant difference in 3-HPA as the bioconversion time increased further. The 3-HPA bioconversion was very rapid, in that about 90% of this product was produced within 0.5 h. The dhaB enzyme, which converts glycerol to 3-HPA and uses vitamin B 12 as a cofactor, is eventually inactivated because the cells cannot regenerate coenzyme B 12 ; instead the catalytic cycle is interrupted by the formation of 5'-deoxyadenosine and the catalytically inactive cobalamin [22], and the altered cofactor remains tightly bound to the active site [23]. A dhaB-reactivating factor in Klebsiella reactivates the inactivated enzyme-bound cyanocobalamin in the presence of free vitamin B 12 , adenosine triphosphate (ATP), and Mg 2+ by mediating the exchange of the tightly bound altered cofactor for a free intact cofactor [24].…”
Section: The Effect Of Conversion Timementioning
confidence: 99%
“…They reactivate the inactivated holoenzymes by mediating the exchange of a damaged cofactor for intact AdoCbl through a molecular‐chaperone‐like mechanism [13,14,16,18]. Recently, we reported evidence for multiple turnovers with diol‐dehydratase‐reactivating factor which demonstrated that the reactivating factor is an enzyme ‘reactivase’ [19].…”
Section: Introductionmentioning
confidence: 99%
“…These cases were largely consistent with existing experimental data, where they were available. An example of a positive result is the agreement between our predictions and structural data relating to the reactivation mechanism of the diol dehydratase [ 80 ].…”
Section: Discussionmentioning
confidence: 71%
“…Although no structural information about this complex in Salmonella is available, crystal structures of highly similar homologs from Klebsiella oxytoca have been solved [ 22 , 78 , 79 ]. Studies with these same homologs demonstrated that the binding mechanism involved a subunit exchange between the dehydratase and the reactivase, where one PduH subunit is released from the reactivase and replaced by one PduD subunit [ 80 ].…”
Section: Resultsmentioning
confidence: 99%